Cytokinesis in trypanosomes. - Farr, H; Gull, K (2012)
Cytokinesis is a crucial step in the cell division cycle whereby the cell membrane and underlying cortex is remodelled and drawn together to create two new daughter cells. While in many eukaryotic systems this process is accomplished by an actomyosin contractile ring, the protozoan parasite Trypanosoma brucei displays an unusual mechanism for cytokinesis, with an increased reliance on microtubules. There are a number of crucial preparatory steps involving the replication and segregation of organelles that must be undertaken in order for cytokinesis to occur. In this review, we will discuss the cellular architecture of the trypanosome and its importance within cytokinesis, and the recent progress in understanding the regulatory systems involved. Recent advances in three-dimensional imaging techniques have improved our understanding of the mechanisms driving cytokinesis and are likely to yield further insights in the future.